Temporal synchronization elicits enhancement of binocular vision functions - Eisen-Enosh, Auria; Farah, Nairouz; Polat, Uri; Mandel, Yossi (iScience, 2023)
Integration of information over the CNS is an important neural process that affects our ability to perceive and react to the environment. The visual system is required to continuously integrate information arriving from two different sources (the eyes) to create a coherent percept with high spatiotemporal precision. Although this neural integration of information is assumed to be critical for visual performance, it can be impaired under some pathological or developmental conditions. Here we took advantage of a unique developmental condition, amblyopia (“lazy eye”), which is characterized by an impaired temporal synchronization between the two eyes, to meticulously study the effect of synchronization on the integration of binocular visual information. We measured the eyes’ asynchrony and compensated for it (with millisecond temporal resolution) by providing time-shifted stimuli to the eyes. We found that the re-synchronization of the ocular input elicited a significant improvement in visual functions, and binocular functions, such as binocular summation and stereopsis, were regained. This phenomenon was also evident in neurophysiological measures. Our results can shed light on other neural processing aspects and might also have translational relevance for the field of training, rehabilitation, and perceptual learning. [Display omitted] •Binocular asynchrony in amblyopic subjects was measured and compensated for•Binocular synchronization improved visual functions in amblyopes•Binocular desynchronization decreased visual functions in neurotypical subjects•Improvement was evident in psychophysical and neurophysiological measures Biological sciences; Neuroscience; Sensory neuroscience